1991
DOI: 10.1111/j.1432-1033.1991.tb16441.x
|View full text |Cite
|
Sign up to set email alerts
|

Site‐directed mutagenesis of the dihydrolipoyl transacetylase component (E2p) of the pyruvate dehydrogenase complex from Azotobacter vinelandii

Abstract: (Receivcd May 13, 1991) -EJB 91 0615Site-directed mutagenesis was performed in the protease-sensitive region, between the lipoyl and catalytic domains and in the catalytic domain, of the dihydrolipoyl transacetylase component (E2p) of the pyruvate dehydrogenase complex from Azotobacter vinelandii. The interaction of the mutated enzymes with the peripheral components pyruvate dehydrogenase (Elp) and lipoamide dehydrogenase (E3) was studied by gel filtration experiments, analytical ultracentrifugation and recons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
26
0

Year Published

1992
1992
2002
2002

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 43 publications
3
26
0
Order By: Relevance
“…These experiments confirm our previous conclusion [14], based on site-directed mutagenesis, that the E l p sites consist of amino acids derived from both the binding and the catalytic domain. The point mutations Lys367 -P Gln (binding domain) and Arg416 --f Asp (catalytic domain) dramatically decreased the affinity for Elp, but not for E3 at catalytically significant ratios.…”
Section: Binding Of Peripheral Components To Chimeric E2p Proteinssupporting
confidence: 80%
See 4 more Smart Citations
“…These experiments confirm our previous conclusion [14], based on site-directed mutagenesis, that the E l p sites consist of amino acids derived from both the binding and the catalytic domain. The point mutations Lys367 -P Gln (binding domain) and Arg416 --f Asp (catalytic domain) dramatically decreased the affinity for Elp, but not for E3 at catalytically significant ratios.…”
Section: Binding Of Peripheral Components To Chimeric E2p Proteinssupporting
confidence: 80%
“…Competition exists between E3, added in excess with respect to its own sites, and E l p for binding to the E l p sites. This is not merely a steric effect due to occupation of the binding domain, because the mutations at the N-terminal part of the catalytic domain also affected E3 binding, when added in excess [14]. On the other hand, it could be shown that the peripheral components do not bind to the isolated catalytic domain of A .…”
mentioning
confidence: 87%
See 3 more Smart Citations